1991
DOI: 10.2135/cropsci1991.0011183x003100030017x
|View full text |Cite
|
Sign up to set email alerts
|

Grain Phytic Acid and Protein are Highly Correlated in Winter Wheat

Abstract: Phytic acid (myo‐inositol hexakisphosphate), the major storage form of P in seeds, is believed to have a negative impact on nutritional quality. Since breeding for low phytic acid has been proposed for several cereals and legumes, it is important to predict the effects of selection against phytic acid on other major grain components. Experiments were conducted to determine the quantitative relationship between grain phytic acid P, total P, and protein in two winter wheat (Triticum aestivum L.) populations, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
3
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 0 publications
12
45
3
5
Order By: Relevance
“…Khan et al (1991) reported very high levels Results obtained in this study showed a linear relation between phytic acid and total phosphorus. Raboy et al (1991) concluded that, in various seeds, phytic acid positively correlates with total phosphorus, correlation coefficients for some cultivars being greater than 0.90. Factors that affect the total phosphorus content, such as soil, available phosphorus and fertilizers, can influence the phytic acid concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Khan et al (1991) reported very high levels Results obtained in this study showed a linear relation between phytic acid and total phosphorus. Raboy et al (1991) concluded that, in various seeds, phytic acid positively correlates with total phosphorus, correlation coefficients for some cultivars being greater than 0.90. Factors that affect the total phosphorus content, such as soil, available phosphorus and fertilizers, can influence the phytic acid concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of germplasm collections have revealed significant genetic variation for both seed phytate and/or total P in common bean, lentil, sorghum, soybean, and wheat (Lolas and Markakis 1975;Raboy et al 1991;Israel et al 2006;Kayode et al 2006;Ficco et al 2009;Thavarajah et al 2010;Akond et al 2011). Likewise, researchers have used both chemical and physical mutagens to isolate lp mutants in barley (Raboy 2000;Bowen et al 2006), common bean (Campion et al 2009), maize (Raboy 2000;Badone et al 2010), rice (Larson et al 2000;Raboy 2000;Rutger et al 2004;Liu et al 2007;Kim et al 2008), soybean (Wilcox et al 2000;Walker et al 2006), and wheat (Guttieri et al 2004).…”
Section: Mining Germplasm Collections For Natural Variation For Sementioning
confidence: 99%
“…Phytic acid concentrations in seeds from a given species vary because of many factors including cultivars (2,13,17), soil conditions, fertilizer applications (3) and moisture plus other climate factors (9). lott et al (12) have reported that the range for phytic acid in cereal grains is 0.86-1.06%, while Reddy et al (18) have obtained values between 0.50 and 1.89%.…”
Section: Resultsmentioning
confidence: 99%